Analisis Transaksi Ijon Dalam Perspektif Pembelajaran Ulumul Hadis - Mohamad Syakur Rahman; Muhammad Sabir (IAIN Manado, 2023)
Analysis of Ijon Transactions in Ulumul Hadith Learning. Transaction problems that occur in society are increasingly widespread, one of which is the practice of ijon transactions (transactions of plants, fruit or seeds that are not ready for harvest). This practice is not only happening at this time, but has existed since the time of the Prophet. Ijon transactions are transactions of fruits or seeds whose maturity or maturity has not been shown, so they are still vulnerable to pests or damage. One of them is that there are transactions that are prohibited in Islam which are grouped into four, namely forbidden because of expert (contract expert), forbidden because of sighat (consent and qabul), forbidden because of ma'qud alaih (sales goods), and forbidden because of syara' (provisions).The law of transactions in Islam is originally mubah (permissible) but if there are things in it that conflict with the Shari'a, then the transaction may become unlawful. For example selling goods that are not owned or goods whose quality and size are unknown. This debt bondage transaction is still very common in the community. This practice applies more to fruits, seeds and other plants exist, but not as much to fruits. Therefore, in this paper the author refers to the discussion of debt bondage transactions in the perspective of Ulumul Hadith learning